GEMAS (Reading and Writing Movement): Optimizing Reading and Writing Literacy Culture at Elementary School N 6 Manukaya - Apricillia, Ni Nengah Diah Elsa; Yuniari , Desak Putu; Trisnawati, Dewa Ayu; Putra, I Wayan Riski Ananda; Maharani , Dewa Ayu Nita; Werang, Basilius Redan (Formosa Journal of Applied Sciences, 2024)
The aim of this research is to describe the implementation of the GEMAS (Reading and Writing Movement) program as an effort to improve students' reading and writing literacy at SD Negeri 6 Manukaya. The research approach used is a qualitative approach. The type of research used is descriptive. Descriptive research is research that attempts to describe phenomena that occur in a real, realistic, actual and current manner. GEMAS is a program that aims to increase interest in reading and the culture of reading and writing among students at SD N 6 Manukaya. This program is implemented with various activities, such as Book Club, Sustainable, and Library Revitalization. Even though the GEMAS program has many benefits, such as increasing enthusiasm for learning, expanding knowledge, and fostering interest in reading and writing, its implementation still faces several obstacles, such as a lack of school facilities and infrastructure, and a lack of communication between schools and parents.